THE INFLUENCE OF CONTENT OF LIPOPROTEINS ON THE STRUCTURAL AND FUNCTIONAL CHANGES OF THE MYOCARDIUM IN CHRONIC HEART FAILURE WITH OVERWEIGHT AND OBESITY - Bidzilya, P. (World of Medicine and Biology, 2016)
The influence of the content of high (HDL-C) and low density lipoproteins cholesterol (LDL-C) on the structural and functional changes of the myocardium in chronic heart failure (CHF) with overweight and obesity were investigated. There is no significant influence of HDL-C level on the structural state of the heart. At low concentration of LDL-C is detected more significant dilatation of all heart chambers and left ventricle hypertrophy (LVH). Patients with normal values of LDL-C occupy an intermediate position according to the severity of structural changes of the myocardium. The high content of LDL-C is accompanied by minimal dilatation of the heart chambers and the degree of LVH. Was not observed dependence of the functional state of the myocardium from the level of lipoproteins
Keywords: chronic heart failure; structural and functional myocardial chances; excess weight; lipoproteins level